Integrated Car Park System for Smart Parking Solution - Harprith Kaur, Randhawa; Deshinta, Arrova Dewi; Nirmal, Kumar Karmani (INTI International University, 2019)
This paper studies a smart parking solution by implementing an integrated car park system using the Internet of Things (IoT) technology that is combined with an android application. The proposed system enables users using android devices to view the current state of the car park (vacant/occupied slots) and reserve a parking lot. Subsequently, the system automatically generates a unique QR code for each booking that allows users to enter and exit the car park. The proposed system also includes e-wallet capabilities for automatic payment at the exit gate. A microcontroller with sensors to monitor the current state of the parking lot are adopted for this purpose, as well as control a mechanism to physically reserve a parking lot for the users. The system will greatly streamline the parking process as users will be able to monitor the car park availability beforehand and this will help combat the issues related to the search of a parking lot.